2015
DOI: 10.1038/gene.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies HLA 8.1 ancestral haplotype alleles as major genetic risk factors for myositis phenotypes

Abstract: Autoimmune muscle diseases (myositis) comprise a group of complex phenotypes influenced by genetic and environmental factors. To identify genetic risk factors in patients of European ancestry, we conducted a genome-wide association study (GWAS) of the major myositis phenotypes in a total of 1710 cases, which included 705 adult dermatomyositis; 473 juvenile dermatomyositis; 532 polymyositis; and 202 adult dermatomyositis, juvenile dermatomyositis or polymyositis patients with anti-histidyl tRNA synthetase (anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 46 publications
3
89
0
1
Order By: Relevance
“…Recently, two large HLA imputation studies confirmed that HLA‐DRB1*03:01 and HLA‐B*08:01 , two alleles inherited together on the 8.1 AH, are strongly associated with MSs . Nevertheless, authors reported contrasting results when analyzed HLA alleles according to specific autoimmune phenotype.…”
Section: The 81 Ah and Aidsmentioning
confidence: 99%
“…Recently, two large HLA imputation studies confirmed that HLA‐DRB1*03:01 and HLA‐B*08:01 , two alleles inherited together on the 8.1 AH, are strongly associated with MSs . Nevertheless, authors reported contrasting results when analyzed HLA alleles according to specific autoimmune phenotype.…”
Section: The 81 Ah and Aidsmentioning
confidence: 99%
“…We enrolled 6270 control subjects without history of autoimmune diseases (mean age, 57.0±13.8 years; female, 48.2%) through the Biobank project 20. The European subjects (21 CADM cases) were recruited as part of an international myositis genetics consortium (MYOGEN),17 and four controls for each case (84 controls) were matched for ethnicity using principal components analysis (PCA) coordinates 21…”
Section: Methodsmentioning
confidence: 99%
“…98 MHC SNPs have also been strongly associated with disease susceptibility in patients with poly- and dermatomyositis, as have risk loci at PLCL1, BLK and CCL21 . 99,100 Substantial overlap in risk loci exists between the aforementioned CTDs and patients with Sjogren's syndrome (SS), which can result in several types of lung pathology, including ILD. In a GWAS of patients with SS, risk loci were again identified within MHC genes, along with IRF5, BLK and STAT5 .…”
Section: Disease-specific Pharmacogenetic Biomarkersmentioning
confidence: 99%